Assessment of energy expenditure in elite jockeys during simulated race riding and a working day: implications for making weight - Wilson, G.; Sparks, S. A.; Drust, B.; Morton, J. P.; Close, G. L. (Applied Physiology, Nutrition, and Metabolism, 2013)
Professional jockeys are unique amongst weight-making athletes in that they are required to make weight on a daily basis by often using potentially hazardous methods, such as food deprivation, dehydration, and forced vomiting. To allow the prescription of accurate energy intake (EI), it is essential to understand the energy requirements of jockeys; however, these data are currently not known. Therefore, we measured the energy expenditure (EE) of professional jockeys during a simulated race ride and for a working day (nonracing) that involved typical stable duties. The accuracy of 2 portable lightweight devices, the Polar RS400 commercial heart rate monitor (CHRM) and the Actiheart monitor (AH) were initially assessed during 30 min of exercise compared with respiratory gas analysis (GA) (n = 9). No significant difference was observed (p > 0.05) and 95% limits of agreement analysis (LoA) showed that CHRM was more closely related to GA (bias: -0.015; LoA: -0.049, +0.019 MJ) than AH (bias: -0.007; LoA: -0.073, +0.059 MJ). A laboratory-based 2-mile (3.2-km) racing protocol was created and EE was assessed using CHRM, GA, and AH. We report that a typical race expends 0.18 (SD ±0.03) MJ. Finally, in a separate group of jockeys (n = 8), 24-h EE was assessed using CHRM. The mean (±SD) EE for a typical day was 11.26 (±1.49) MJ. Additionally, we measured EI using 7-day self-reporting food record diaries. Mean EI was 7.24 (±0.92) MJ, largely consumed as 2 main meals. These data provide a platform to implement dietary strategies that create appropriate weight-loss targets and therefore improve the physical and mental well-being of professional jockeys.